Inferring Mental States from Brain Data: Ethico‐legal Questions about Social Uses of Brain Data - Chandler, Jennifer A. (The Hastings Center report, 2025)
Neurotechnologies that collect and interpret data about brain activity are already in use for medical and nonmedical applications. Refinements of existing noninvasive techniques and the discovery of new ones will likely encourage broader uptake. The increased collection and use of brain data and, in particular, their use to infer the existence of mental states have led to questions about whether mental privacy may be threatened. It may be threatened if the brain data actually support inferences about the mind or if decisions are made about a person in the belief that the inferences are justified. This article considers the chain of inferences lying between data about neural activity and a particular mental state as well as the ethico‐legal issues raised by making these inferences, focusing here on what the threshold of reliability should be for using brain data to infer mental states.